Influence of Cell Membrane Wrapping on the Cell−Porous Silicon Nanoparticle Interactions. Issue 17 (29th July 2020) - Fontana, Flavia; Lindstedt, Hanna; Correia, Alexandra; Chiaro, Jacopo; Kari, Otto K.; Ndika, Joseph; Alenius, Harri; Buck, Jonas; Sieber, Sandro; Mäkilä, Ermei; Salonen, Jarno; Urtti, Arto; et al.
Abstract: Biohybrid nanosystems represent the cutting‐edge research in biofunctionalization of micro‐ and nano‐systems. Their physicochemical properties bring along advantages in the circulation time, camouflaging from the phagocytes, and novel antigens. This is partially a result of the qualitative differences in the protein corona, and the preferential targeting and uptake in homologous cells. However, the effect of the cell membrane on the cellular endocytosis mechanisms and time has not been fully evaluated yet. Here, the effect is assessed by quantitative flow cytometry analysis on the endocytosis of hydrophilic, negatively charged porous silicon nanoparticles and on their membrane‐coated counterparts, in the presence of chemical inhibitors of different uptake pathways. Principal component analysis is used to analyze all the data and extrapolate patterns to highlight the cell‐specific differences in the endocytosis mechanisms. Furthermore, the differences in the composition of static protein corona between naked and coated particles are investigated together with how these differences affect the interaction with human macrophages. Overall, the presence of the cell membrane only influences the speed and the entity of nanoparticles association with the cells, while there is no direct effect on the endocytosis pathways, composition of protein corona, or any reduction in macrophage‐mediated uptake. Abstract : Cellular internalization pathways of biohybrid nanoparticles are compared to conventional nanosystems in presence of inhibitors of the uptake, resulting in faster association promoted by the biohybrid particles, without differences in the uptake mechanism. Furthermore, the protein corona composition, interactions with cells of the innate immune system, and circulation time in Zebrafish are similar between biohybrid and conventional nanoparticles.